Perencanaan Tebal Perkerasan Kaku dan Rencana Anggaran Biaya Jalan Tani Desa Hative Besar Kota Ambon: Rigid Pavement Thickness Planning and Budget Plan of Farm Road in Hative Besar Vilage Ambon City - Kailul, Suli; Siahaya, Vera Th. C.; Saleh, La Mohamat (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Rigid Pavement is a pavement construction with coarse aggregate raw materials and uses cement as a binder, so it has a relatively high level of rigidity. This study aims to determine the thickness of rigid pavement of peasant road planning with the 2017 road pavement design manual method required in the construction of Hative Besar Village peasant road in Ambon City, and determine the amount of Budget Plan in the calculation of peasant road pavement in Hative Besar Village, Ambon City. The results showed that, rigid pavement planning on the Hative Besar Village Farmer's Road in Ambon City (STA 0+000 - 1+200) with a length of 1.2 km, based on LHR data for the 2023 plan year with a pavement plan age of 40 years, the cement concrete pavement of the connected type without reinforcement was obtained 2.85 cm thick, 10 cm Lean concrete foundation and Class A Aggregate Foundation Layer was obtained 15 cm thick. and the results of the calculation of the Budget Plan for the cost of excavation of foundation soil, sand backfill under the foundation, river stone masonry, sand backfill under the floor, empty stone masonry, and K-250 concrete rebate amounted to Rp 2,290,560,000 (Two Billion Two Hundred Ninety Million Five Hundred Sixty Thousand Rupiah).